THE INFLUENCE DEBT TO EQUITY RATIO (DER), EARNING PER SHARE (EPS), COMPANY SIZE, ACCOUNTING PROFIT AND RETURN ON ASSET (ROA) ON STOCK RETURN IN FOOD AND BEVERAGE SUB SECTOR COMPANIES IN 2017-2021 - Isendi, Alvin; Rachmawati, Lia; Rakhmawati, Ratih (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2023)
This study aims to analyze the effect of DER, EPS, company size, accounting profit and ROA on stock returns in food and beverages sub-sector listed on the Indonesia Stock Exchange (IDX) in 2017-2021. The type of research used a quantitative research. The data used is secondary data in the form of financial reports and annual reports of food and beverage sub sector companies listed on Indonesia Stock Exchange (IDX) in 2017-2021. The data analysis method used is descriptive statistics, clasical assumption test, multiple linear regression analysis, hypothesis testing and determination coeficient test. The result showed that DER, accounting profit and ROA had a partial effect on stock returns, While EPS and company size have no partial effect on stock returns. Simultaneously DER, EPS, company size, accounting profit and ROA have an effect on stock returns. Keywords: DER, EPS, Company Size, Accounting Profit, ROA, Stock Return